Handbook of mold, tool and die repair welding - Thompson, Steve, 1955- (William Andrew Pub., 1999)
Guide to the repair of molds, tools, and dies. Offers advice for companies wishing to become self-sufficient in in-house tool repair work, from buying the most suitable equipment and materials to using them effectively. Provides basic TIG welding exercises for beginners and simple, step-by-step advice on essential weld techniques.
Includes index.
Keywords: Electric welding -- Handbooks, manuals, etc.; Tools -- Maintenance and repair.; Dies (Metal-working) -- Maintenance and repair.; elektronické knihy; electronic books